DISPLACEMENT AND CREATIVE REPRESENTATIONS OF KASHMIR IN VARIOUS NOVELS - 528, Mr. Kuldeep Singh, Ms.Amandeep Kaur (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
The aim of this paper is that literature, by virtue of its inherent representational nature, deals directly or indirectly with human problems specific to a certain environment and time. The nature of form and content of creative expression in harsh situations of violence induced by sectarian schisms, cultural collapse, and aggressive politics may be seen in contemporary literature on Kashmir. Many writers have tackled various subjects in modern literature about Kashmir, but no single writer has produced major work, hence it is necessary for the scope of my research to include several writers. Forced displacement has been a unifying experience for Kashmiris all over the world, enhancing their awareness of their identity as Kashmiris. As a result, refugees have played an important role in reminding their fellow citizens of the territory's social and political dislocation. The primary goal of this research was to examine some of the most representative stories, poetry, and novels accessible in Kashmiri and English in relation to various social, cultural, and psychological variables that contributed to the turbulence that enveloped an entire valley and shook it to its core.